ANALISIS KINERJA KEUANGAN DAERAH KOTA SAMARINDA TAHUN 2013-2014 - Suyatin Suyatin (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
This research is meant to know and analize the performance of the finance of the local goverment , Samarinda , in the year 2013-2014. The tools of the analisis used is racional one which consists of the level of decentralization , the dependence of the local government finance  , the self-standing , effectivity of the original government income and local government tax.The result of the research is that the ability of the local government concerned in the realization of decentralization is better if it is seen from the improvement of it. .The level of the dependence of the finance is smaller and smaller and the self-effort  is higher though the mobilazation of the receipt of the original income goes down where in 2014 is not effective .The local government in collecting tax is good enough either in 2013 or in 2014.So it can be concluded generally that the performance of the team goes better in 2014